Implikacje rozwoju infrastruktury drogowej dla rynku pracy - teoria i rzeczywistość (na przykładzie województwa łódzkiego) - Kryńska, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper attempts to answer a twofold question whether and what influence the development of road infrastructure will have on rise in demand for labour and fall in unemployment in the Lodz Region. Analyses of the regional labour market show that although the threat of unemployment decreases, its level is still very high. One of the reasons for imbalances on the labour market of the Lodz Province is underdevelopment of technical infrastructure, and particularly the road system which determines both the influx of foreign capital and the business climate. The theoretical part of our investigation shows explicitly that outlays on technical infrastructure may result in a considerable economic recovery of the region, and consequently, an improvement in the situation on the labour market. The paper concludes with the statement that the development of road infrastructure in the Lodz Region will definitely lead to a decrease in unemployment. However, it is difficult to predict the scale of the change as it depends on several other factors which determine the region's capacity to attract and retain the foreign capital. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 38-48